2015
DOI: 10.1016/j.lwt.2014.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of refrigerated storage in nitrogen-enriched atmospheres on the microbial quality, content of bioactive compounds and antioxidant activity of sauerkrauts

Abstract: a b s t r a c tThe aim of this work was to investigate the influence of storage at 4 C in conventional or nitrogen (N 2 )-enriched atmospheres for 3 months on the microbial status of sauerkraut obtained by natural fermentation or by Leuconostoc mesenteroides inoculation. The content of vitamin C, glucosinolate derivatives and the antioxidant activity of stored sauerkrauts were also evaluated. Aerobic/anaerobic mesophilic bacteria and lactic acid bacteria populations decreased sharply during N 2 storage, whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Various technological treatments such as cooking, pre-processing (washing, peeling, grinding) and storage may lead to signifi cant reductions in antioxidants. Vitamin C is highly labile and long--term storage, high temperatures and physical or chemical damage of the product have a negative infl uence on its content [Peñas et al, 2015]. Preliminary treatment of vegetables leads also to enzymatic decomposition of total polyphenols or their decomposition due to the presence of oxygen.…”
mentioning
confidence: 99%
“…Various technological treatments such as cooking, pre-processing (washing, peeling, grinding) and storage may lead to signifi cant reductions in antioxidants. Vitamin C is highly labile and long--term storage, high temperatures and physical or chemical damage of the product have a negative infl uence on its content [Peñas et al, 2015]. Preliminary treatment of vegetables leads also to enzymatic decomposition of total polyphenols or their decomposition due to the presence of oxygen.…”
mentioning
confidence: 99%
“…by 3% in broccoli, by 4% in caulifl ower and by 34.1% in zucchini after 7 days of storage at 4°C, compared to fresh vegetables. On the other hand, no signifi cant changes of the antioxidant activity were observed by Peñas et al [2015], during the storage of naturally obtained sauerkraut both at conventional and N 2 -enriched atmospheres. Kusznierewicz et al [2010] observed that the process of fermentation increased 3-4-fold the antioxidant activity of cabbage.…”
Section: Antioxidant Activitymentioning
confidence: 82%
“…Among non-nutritive compounds, it can be highlighted the presence of fi ber, which is positively affecting intestinal peristalsis and goitrogens which have a negative effect on the human body. The latter, reducing the iodination of tyrosine, can lead to hypothyroidism [Girgin & El Nehir, 2015; KapustaDuch et al, 2012; Peñas et al, 2015]. Sauerkraut, despite the losses of some compounds during fermentation, retains a high nutritional value and it is additionally enriched with precious compounds positively affecting the consumers' health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value recorded by Peñas et al . () was 20.1 mg/100 g. The level of vitamin C in sour cabbage depends on its amount in the raw material, sauerkraut acidity and storage conditions. In fresh vegetables, this parameter is affected, for example, by species, climatic and agro‐technical conditions and the time of harvest (Grajek ; Peñas et al .…”
Section: Discussionmentioning
confidence: 98%